EVALUASI TINGKAT KESESUAIAN STANDAR AKREDITASI TERHADAP PELAYANAN FARMASI DAN STRATEGI PERBAIKAN DENGAN METODE HANLON DI RSUD KABUPATEN BIMA - Dedent Eka Bimmaharyanto.s; Achmad Fudholi; Gunawan Pamudji Widodo (Jurnal Ilmiah Mandala Education (JIME), 2017)
Getting maximal service represent dream all society especially receiver of service of  the hospital  including in pharmacy installation. Patient got many problems because service not yet fulfilled standard. To fulfill requirement of patient, pharmacy installation have to this research accredit  to know storey level according to seven accreditation standard to service of pharmacy in RSUD Sub Province Bima and repair strategy with Hanlon method.  This Research use instrument of quizioner  Depkes and special informan interview counted 15 informan and people lock counted 3 people. Subject at this research is all officer in concerned and have important role in pharmacy Installation RSUD Sub Province Bima. Conducted by assessment seven standard  later then compared to between informan with result of observation,  afterwards analyzed by strategy development by using Hanlon method. Result of Research of show there are difference of result assessment of standard accredit between officer of pharmacy Installation that is ( 58,75%) with research that is  ( 55%). From seventh of accreditation standard, nothing that fulfill accreditation standard (< 60%), result  strategy development with Hanlon method is Facility and equipments, repair of facilities and basic facilities of Pharmacy administration  management and, immediately do function KFT . Evaluation and quality control, require to make pharmacy program written  and also SK about meeting schedule .Philosophy   and  target, SK about policy of pharmacy service  from  Hospital head. Policy and procedure, making SOP and policy written  about management of provisions of pharmacy . Development of education program and staff,  done by education program and periodical training in IFRS. STAF and head, existence of staff pharmacy performance evaluation and orientation to officer of Installation Pharmacy